Entry and the accumulation of capital: A two state variable extension to the Ramsey model - Brito, Paulo (2009)
In this paper we consider the entry and exit of firms in a dynamic general equilibrium model with capital. At the firm level, there is a fixed cost combined with increasing marginal cost, which gives a standard U-shaped cost curve with optimal firm size. Entry is determined by a free entry condition such that the cost of entry is equal to the present value of incumbent firms. The cost of entry (exit) depends on the flow of entry (exit). Equilibrium is saddle-point stable and the stable manifold is two-dimensional. Transitional dynamics can, under certain circumstances, be non-monotonic.